British Oculoplastic Surgery Society (BOPSS) National Ptosis Survey. Issue 8 (20th June 2008) - Scoppettuolo, E; Chadha, V; Bunce, C; Olver, J M; Wright, M; ,
Abstract : Aim: To assess the results of primary aponeurotic ptosis surgery among UK ophthalmic oculoplastic surgeons, from both the surgeon's and patient's perspective; also to inform and encourage good clinical practice by generating outcomes for individual surgeons, units and for benchmarking purposes. Methods: A prospective, web-based, non-comparative, interventional study was conducted over a period of 1 year commencing January 2005 and ending December 2005. The data-entry sheet for the preoperative, operative and postoperative data was completed and submitted online via the British Oculoplastic Surgery Society website. Surgical results were assessed objectively (by the surgeon) by measuring the upper lid margin reflex distance (uMRD) and the interlid difference in: MRD, lid show, skin crease and lid contour with the outcome graded as: success, partial success or failed. Surgical results were also assessed subjectively (by the patient) with the outcome graded as: completely satisfied, significantly improved, no change or worse than before the operation. Results: Three hundred and sixty-five patients undergoing primary aponeurotic ptosis repair, from 40 different consultant-led teams with a declared oculoplastic interest and expertise, originating from 27 units across the UK were entered into the study. Using objective criteria, success was achieved in 128/223 (57%) cases, with significantly greater degrees of success seen in patients with mild ptosis and for surgeons who performed ptosis surgery more frequently. Using subjective criteria, 184/282 (65%) of patients were completely satisfied, with a further 89/282 (32%) judging themselves significantly improved. The patients' assessment of the surgery was less critical than that of the surgeons: 46/138 (33%) of patients who were completely satisfied and 37/72 (51%) of those who were significantly improved did not meet the criteria for a successful surgical outcome. The re-operation rate was 8/313 (2.6%). Conclusions: The authors have generated a valid series of surgical outcomes both for individuals, units and the UK as a whole, expressed in both objective and subjective terms for what we regard as the signature procedure for an oculoplastic surgeon: aponeurotic ptosis surgery. Individual results have been communicated to our members, which will allow them to compare their results with true peer-group-generated figures and will aid appraisal and ultimately revalidation.